La skholé aristotélica como condición de la excelencia humana - Margarita Mauri (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
The proposal to deal with the scholḗ understood simply as ‘free time’ must start with two questions: free time of which kind of activities? and free time for what kind of activities? Aristotle’s exposition tries to answer both questions. The implicit conceptual assumptions that the author uses when offering answers are the following: a) the teleological ordering of human activities; b) the excellence necessary to carry them out and; c) the characterization of the two kinds of eudaimonia that appear in the last book of the Nicomachean Ethics (EN). The purpose of this paper is to determine the relationship of the concept of scholē´ with other concepts of the Aristotelian practical philosophy and to distinguish the different contents of the word scholḗ.